Venetian or Adriatic? Refocusing the Geography of Late-Medieval Stone Sculpture in the central Adriatic Basin: Four Case Studies - Palozzi, Luca (Hortus Artium Medievalium, 2014)
Abstract Since at least 1976 and the publication of Wolfgang Wolters’ La scultura veneziana gotica (1300-1460), art historians and the general public have been familiar with the label ‘Venetian sculpture’. As often happens with winning paradigms, however, even this ostensibly straightforward label risks being misused. We might in fact succumb to the paradox of interpreting most of the sculptural production of the late-medieval period in the Northern and Central Adriatic Basin as ‘Venetian’ or as ‘influenced by Venice’. Yet, this is not always the case. By discussing four lesser-known Central Adriatic case studies, this article highlights the need to begin to speak of an ‘Adriatic sculpture’ of the late-medieval period.